SERIGALA BERBULU DOMBA : DAMPAK KERJASAMA EKONOMI CINA-MADAGASKAR PADA PEKERJA ANAK PERTAMBANGAN MIKA - Ratu Fadilah Audzitni Rao (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2022)
China and Madagascar established diplomatic relation since 1972 with sharing One China Policy among African nations as the main agenda. In 1990’s a significant shift occurred in Madagascar economic system where the Madagascar government decided to liberalized its economic system and it bring a massive change between China-Madagascar relation. It began from Development Assistant where China began to support aid to Madagascar for its development, from loan, education, assistance and any other aid were given to Madagascar with some requirements specially to open its trade, market and support economic cooperation between both countries. Therefore the cooperation between both countries changed and focus more on economic cooperation. Madagascar which rich for its natural resources spark interest among Chinese investors. Chinese entrepreneurs and companies began investing and cooperate in mining Madagascar’s natural resources especially mica. Mica itself is one of mineral that processed through mining, it could be found in everyday life from the makeup that we wear to electronic stuff. In 2017 Madagascar mica export to China reach up to 87%, the mica mostly sent to big companies such as Ningbo Ram Eletric Material Ltd, Dongguan City Non Cloud Mines Ltd and other and the number keep increasing. Investigation in 2019 found out that there is massive exploitation in mica industries. There are more than 10.000 mica mines child laborers that started from 4 years old in Madagascar, they work without any security check and guard from the companies and experiencing wages and other exploitation. Previously there has been some researches about mica mining by child laborers in Madagascar but none of the researches intertwines the connection between China-Madagascar cooperation with the child laborers in Madagascar. This qualitative research with desk research method aims to explain how China-Madagascar Cooperation rises mica mines child laborers and international response related to the issue. This research uses the dependency theory to explain the research result which mica cooperation between the two countries increase mica child labour in Madagaskar.